2002
DOI: 10.1016/s0092-8674(02)00906-6
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Mechanism of Integrin αIIbβ3 “Inside-Out” Activation as Regulated by Its Cytoplasmic Face

Abstract: Activation of the ligand binding function of integrin heterodimers requires transmission of an "inside-out" signal from their small intracellular segments to their large extracellular domains. The structure of the cytoplasmic domain of a prototypic integrin alpha(IIb)beta(3) has been solved by NMR and reveals multiple hydrophobic and electrostatic contacts within the membrane-proximal helices of its alpha and the beta cytoplasmic tails. The interface interactions are disrupted by point mutations or the cytoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
579
3
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(610 citation statements)
references
References 52 publications
24
579
3
2
Order By: Relevance
“…These cells are often metabolically quiescent, and tend to regulate their integrins to exist in a low affinity state, as shown by protein conformation and ligand-binding investigations. [82][83][84][85] These conformational changes exist in the extracellular ligand-binding domains and the cytoplasmic domain, 86 which may influence the capacity to influence apoptosis and cell survival. However, the expression of hematopoietic cellspecific proteins, as well as the quiescent metabolism of these cells, likely also contributes to cell survival in the absence of a substrate ligand.…”
Section: Signaling Cascades and The Integrin Rheostatmentioning
confidence: 99%
“…These cells are often metabolically quiescent, and tend to regulate their integrins to exist in a low affinity state, as shown by protein conformation and ligand-binding investigations. [82][83][84][85] These conformational changes exist in the extracellular ligand-binding domains and the cytoplasmic domain, 86 which may influence the capacity to influence apoptosis and cell survival. However, the expression of hematopoietic cellspecific proteins, as well as the quiescent metabolism of these cells, likely also contributes to cell survival in the absence of a substrate ligand.…”
Section: Signaling Cascades and The Integrin Rheostatmentioning
confidence: 99%
“…Inside-out signalling involves an internal signal binding to the cytoplasmic tail of integrins, which then promotes conformational changes in the heterodimer and influences the affinity of integrin for its ECM ligand (Takagi et al 2001;Vinogradova et al 2002). Both the TM domains and cytoplasmic tails play a role during inside-out signalling.…”
Section: Bidirectional Signallingmentioning
confidence: 99%
“…The function of the cytoplasmic tails during integrin activation is to facilitate the binding of integrin adaptor proteins, such as talin and kindlin, via NxxY motifs (Calderwood et al 1999). Upon adaptor protein binding, the cytoplasmic tails separate along with the TM domains, which destabilises the tail-head interface and facilitates the 'switchblade'-like opening, causing the hybrid domain to swing out and integrin to enter the high-affinity or active conformation Vinogradova et al 2002;Xiao et al 2004;Luo et al 2007). In this 'active' extended conformation with open headpiece, integrins are able to bind extracellular ligands, which further stabilises the integrin heterodimer and eventually leads to integrin clustering, intracellular kinase recruitment and activation of downstream signalling pathways ).…”
Section: Bidirectional Signallingmentioning
confidence: 99%
“…This data combined with NMR and electron-microscopic imaging have suggested that the integrin heterodimeric receptor behaves as an allosteric switch between a freely diffusing plasma membrane protein and a bivalent linker protein, binding simultaneously to extracellular ligands and cytoplasmic adaptor proteins [4,20,21]. Although there are important structural differences between the Idomain containing and I-domain lacking αβ-integrin heterodimers (Table 1), the proposed ligand-bindinginduced allosteric switch is remarkably similar, perpetuated by the displacement of an α-helix on the surface of the α-chain I-domains or β-chain I-like domains [4,22].…”
Section: Integrin Affinity and Avidity Modificationsmentioning
confidence: 99%
“…Fast integrin turnover is illustrated by circular arrows; polarized integrin turnover in sliding focal contacts is illustrated by a circular-straight arrow; immobilized integrins in focal complexes are illustrated by vertical arrows onto the membrane proximal domains, such that the respective α-and β-transmembrane domains would lay in close proximity [19]. Furthermore, this closed, tightly packed conformation is stabilized by electrostatic interactions (salt bridge) in the membraneproximal cytoplasmic tail regions of the respective α-and β-subunits [20,23]. In this folded-up, inactive structure of the αvβ 3 -integrin, the ligand-binding pocket is facing the plasma membrane, potentially only accessible by soluble and small ligands.…”
Section: Integrin Affinity and Avidity Modificationsmentioning
confidence: 99%